205k views
0 votes
Simplify the given equation.

17x - 6 + 3x - 5 = x + 11 + 4x

A. 20x - 11 = 5x + 11
B. 20x + 1 = 5x + 11
C. 9x = 16x

User Nikea
by
5.3k points

2 Answers

5 votes
A option is right ..........
User Fasouto
by
5.5k points
7 votes
Okay, so, the first thing you should do is: group what has "x" and what doesn't .
Like this:
17x+3x-6-5=4x+x+11

Now... solve the + and -:
17x+3x -6-5 = 4x+x +11
(20x) (-11) = 5x +11

20x-11=5x+11

So, correct answer is A.

User Phatblat
by
6.9k points